Return to Play After Soleus Muscle Injuries. Issue 7 (22nd July 2015) - Pedret, Carles; Rodas, Gil; Balius, Ramon; Capdevila, Lluis; Bossy, Mireia; Vernooij, Robin W.M.; Alomar, Xavier
Background: Soleus muscle injuries are common in different sports disciplines. The time required for recovery is often difficult to predict, and reinjury is common. The length of recovery time might be influenced by different variables, such as the involved part of the muscle. Hypothesis: Injuries in the central aponeurosis have a worse prognosis than injuries of the lateral or medial aponeurosis as well as myofascial injuries. Study Design: Case series; Level of evidence, 4. Methods: A total of 61 high-level or professional athletes from several sports disciplines (soccer, tennis, track and field, basketball, triathlon, and field hockey) were reviewed prospectively to determine the recovery time for soleus muscle injuries. Clinical and magnetic resonance imaging evaluation was performed on 44 soleus muscle injuries. The association between the different characteristics of the 5 typical muscle sites, including the anterior and posterior myofascial and the lateral, central, and medial aponeurosis disruption, as well as the injury recovery time, were determined. Recovery time was correlated with age, sport, extent of edema, volume, cross-sectional area, and retraction extension or gap. Results: Of the 44 patients with muscle injuries who were analyzed, there were 32 (72.7%) strains affecting the myotendinous junction (MT) and 12 (23.7%) strains of the myofascial junction. There were 13 injuries involving the myotendinous medial (MTM), 7 affecting the MT central (MTC), 12 the MT lateral (MTL), 8 the myofascial anterior (MFA), and 4 the myofascial posterior (MFP). The median recovery time (±SD) for all injuries was 29.1 ± 18.8 days. There were no statistically significant differences between the myotendinous and myofascial injuries regarding recovery time. The site with the worst prognosis was the MTC aponeurosis, with a mean recovery time of 44.3 ± 23.0 days. The site with the best prognosis was the MTL, with a mean recovery time of 19.2 ± 13.5 days ( P < .05). There was a statistically significant correlation between recovery time and age ( P < .001) and between recovery time and the extent of retraction ( P < .05). Conclusion: Wide variation exists among the different types of soleus injuries and the corresponding recovery time for return to the same level of competitive sports. Injuries in the central aponeurosis have a significantly longer recovery time than do injuries in the lateral and medial aponeurosis and myofascial sites.